1998
DOI: 10.1002/(sici)1099-0518(199802)36:3<461::aid-pola10>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A study of the thermal cure of a phenylethynyl‐terminated imide model compound and a phenylethynyl‐terminated imide oligomer (PETI‐5)

Abstract: ABSTRACT:The kinetic mechanism of the thermal cure of a phenylethynyl-terminated imide model compound, 3,4-bis[(4-phenylethynyl)phthalimido]diphenyl ether (PEPA-3,4-ODA) and a phenylethynyl-terminated imide oligomer PETI-5 (MW 5000 g/mol) was studied. FTIR was used to follow the cure of the model compound, while thermal analyses (DSC) was used to follow the cure of the PETI-5 oligomer. The changes in IR absorbance of phenylethynyl triple bonds at 2214 cm 01 of PEPA-3,4-ODA as a function of cure time were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 0 publications
4
67
0
Order By: Relevance
“…Crosslinking reactions in various resins have been studied by IR spectroscopy [24,25], and FTIR imaging using focal-plane array detection [26].…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…Crosslinking reactions in various resins have been studied by IR spectroscopy [24,25], and FTIR imaging using focal-plane array detection [26].…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…[23][24][25][26][27][28] Solid-state 13 C-NMR, FT-IR and ESR analyses have brought some insight into the cure mechanism of arylacetylene group. The results demonstrated that the arylacetylene group underwent cyclotrimerization, hydrogen addition, DielsAlder cycloaddition, etc., and formed a complex crosslinked structure like condensed polycyclic aromatic structure during the cross-linking process.…”
Section: Methodsmentioning
confidence: 99%
“…Many investigators have utilized a variety of analytical methods to examine the imidization and/or cure of ethynylor phenylethynyl-terminated imide polymers, including, for example, FTIR [19,24,35], DSC [19,23,36], thermogravimetric analysis (TGA) [23], high performance liquid chromatography (HPLC) [4], and solid-state 13 C nuclear magnetic resonance (NMR) [37] methods. Nonetheless, each of the approaches has limitations.…”
Section: Imidization and Cure Reaction Of Peti-5 Impregnated Glass Famentioning
confidence: 99%